Clinical significance of serum anti-GM-CSF autoantibody levels in autoimmune pulmonary alveolar proteinosis. (February 2018) - Nishimura, Masaki; Yamaguchi, Etsuro; Takahashi, Ayumu; Asai, Nobuhiro; Katsuda, Eisuke; Ohta, Toyohiro; Ohtsuka, Yoshinori; Kosaka, Kenshi; Matsubara, Ayako; Tanaka, Hiroyuki; Yokoe, Norihito; Kubo, Akihito; et al.
Aim: Precise clinical significance of antigranulocyte-macrophage colony stimulating factor (GM-CSF) autoantibody levels in autoimmune pulmonary alveolar proteinosis (aPAP) has not been well studied.Methods: We obtained sera from 50 healthy controls, 46 aPAP patients, 50 with sarcoidosis, 52 with idiopathic interstitial pneumonia and 75 with pneumoconiosis. The clinical course of aPAP patients was assessed by scoring computed tomography images in 19 patients.Results: The cut-off level of anti-GM-CSF IgG for discrimination between aPAP and other diffuse lung diseases was 2.8 μg/ml with 100% sensitivity and 98% specificity. Antibody levels at baseline were significantly lower in the improved group than in the unimproved group (p = 0.008).Conclusion: Our results indicate the existence of threshold levels of serum anti-GM-CSF IgG for the development and persistence of aPAP.